"The Dread of Something After Death" - The Relationship Between Shakespeare's Hamlet and Some Medieval Dream Visions and Ghost Stories - Wicher, Andrzej (Studia Anglica Posnaniensia, 2009)
The present article tries to answer the question whether it is possible to think of William Shakespeare's Hamlet as a dream vision in which the Ghost plays the role analogous to the Dreamer's supernatural guide, which is the situation we meet with in medieval dream visions, such as Chaucer's The book of the Duchess, or The Pearl. It seems that such an interpretation is possible, even though it should be approached cautiously because medieval ghosts and dead souls, and other supernatural phenomena, not only in dream visions, usually function as a means to solve, or at least alleviate, a crisis, whereas in Hamlet the Ghost comes rather to exacerbate it, and make it more tragical. To prove this point, the author makes comparisons not only between Hamlet and dream visions, but also some medieval ghost stories, and the thirteenth century romance Havelok the Dane, which is based on a narrative pattern not very different from that of Hamlet. Another problem examined in this article is that of the extent to which we can talk of the motif of reduplication and monstrous double as a leitmotif in Hamlet, and also in some of its analogues. Some comments and ideas by Frank Kermode and Harold Bloom are made use of in this context.